Penggunaan Media Gambar Manipulatif Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas 2 SD Al-Qur'an Darurrohmah (Full Day School): PTK penelitian tindakan kelas - Lili Nurhidayah; Bambang Ariyanto; Erni Mariana (STKIP Subang, 2026)
Mathematics learning in grade 2 of Al-Qur'an Darurrohmah Elementary School (Full Day School) still shows low learning outcomes due to the learning process that still does not involve concrete media so that students have difficulty in understanding concepts directly. Therefore, it is necessary to use appropriate learning media, one of which is using manipulative image media. This study aims to improve mathematics learning outcomes through the use of manipulative image media in mathematics subjects in grade 2 of Al-Qur'an Darurrohmah Elementary School (Full Day School). This study uses Classroom Action Research (CAR) which is carried out in two cycles, where each cycle consists of planning, implementation, observation, and reflection stages. The subjects of this study were 19 grade 2 students. Data collection techniques were carried out through observation, interviews, documentation, and learning outcome tests. Data were analyzed descriptively quantitatively and qualitatively. The results of the study showed an increase in student learning outcomes after the use of manipulative image media. Learning completion in cycle I was 58% (11 students completed), then increased in cycle II to 84% (16 students completed). Based on the results of the study, it can be concluded that the use of manipulative image media can improve the mathematics learning outcomes of grade 2 students of SD Al-Qur'an Darurrohmah (Full Day School) in the mathematics subject.